Adição de polissacarídeos sulfatados da macroalga marinha Ascophyllum nodosum ao meio diluidor no resfriamento seminal de tambaqui, Colossoma macropomum (Cuvier, 1816) - Apoliano, Marcos Luiz da Silva (2024)
Tambaqui (Colossoma macropomum) is a neotropical fish from the Amazon River basin with high aquaculture potential, being the most produced native fish species in Brazil. In this scenario, research and new technologies are needed to boost the productive growth of the species, especially those related to its reproductive process.Among the biotechnological advances related to the reproduction of this species, the seminal cooling technique stands out. However, this process contributes to oxidative stress and gametic cell damage. As an alternative, it is proposed to add antioxidant compounds to the diluting medium, such as sulfated polysaccharides (PS). Therefore, this work aims to evaluate the effect of using different concentrations of sulfated polysaccharides from the marine macroalga Ascophyllium nodosum on the sperm quality parameters of cooled tambaqui semen. For this, two control treatments were used: T1 (fresh semen) and T2 (semen + powdered coconut water, ACP®-104); and three experimental groups: T3 (semen + ACP®-104 + 0.25 mg.mL-1 of PS), T4 (semen + ACP®-104 + 0.50 mg.mL-1 of PS) and T5 (semen + ACP®-104 + 0.75 mg.mL-1 PS). The samples were subjected to cooling and maintained in this condition for 6, 12, 24, 48 and 72 hours, at a temperature of 4 ºC. During each period, samples were analyzed for total motility, curvilinear velocity (VCL), straight line velocity (VSL), average speed of the route (VAP), morphology, membrane integrity and sperm DNA. After 24 hours, for the in natura treatment, a sudden drop in the values of all sperm parameters studied was observed. While the T2 treatment provided better means of total motility (44.8 ± 10.7%), VCL (55.8 ± 18.7%), VSL (44.4 ± 15.5%), VAP (52 .1 ± 12.7%) and DNA integrity (19.68 ± 1.44%) than treatments supplemented with PS. However, there were no differences in the results of membrane integrity and sperm morphology. There was no difference between fertilization rates for T2 and T5 treatments after 24 hours of cooling compared to fresh semen. The results suggest that supplementation with PS from the marine macroalga A. nodosum is not capable of maintaining the quality of all sperm parameters of tambaqui semen stored for different times at 4 ºC. Furthermore, it is possible to conclude that the addition of 0.75 mg.mL-1 of PS promotes improvements in the fertilization rate within 24 hours of tambaqui seminal cooling, therefore, its addition is recommended to maintain the fertilizing capacity of sperm of the species.